2017
DOI: 10.1080/15384101.2017.1321180
|View full text |Cite
|
Sign up to set email alerts
|

The human mitochondrial Hsp60 in the APO conformation forms a stable tetradecameric complex

Abstract: The human mitochondrial chaperonin is a macromolecular machine that catalyzes the proper folding of mitochondrial proteins and is of vital importance to all cells. This chaperonin is composed of 2 distinct proteins, Hsp60 and Hsp10, that assemble into large oligomeric complexes that mediate the folding of non-native polypeptides in an ATP dependent manner. Here, we report the bacterial expression and purification of fully assembled human Hsp60 and Hsp10 recombinant proteins and that Hsp60 forms a stable tetrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Each Hsp60 revealed a single peak with elution volume of 8.34-8.57 mL (corresponding molecular weight: 1,044,000-924,000). We conclude that both Hsp60 WT and GW are stable tetradecamers, supporting a previous report [35]. Taken together with the results of GroEL G192W [24,30], we concluded that Hsp60 G190W had the open-mimic conformation of AD, similar to GroEL G192W, with hydrophobic characteristics that probably enhanced the amyloid fibrillation suppression effect.…”
Section: Hsp60 Gw Shows An Increased Degree Of Surface Hydrophobicitysupporting
confidence: 89%
“…Each Hsp60 revealed a single peak with elution volume of 8.34-8.57 mL (corresponding molecular weight: 1,044,000-924,000). We conclude that both Hsp60 WT and GW are stable tetradecamers, supporting a previous report [35]. Taken together with the results of GroEL G192W [24,30], we concluded that Hsp60 G190W had the open-mimic conformation of AD, similar to GroEL G192W, with hydrophobic characteristics that probably enhanced the amyloid fibrillation suppression effect.…”
Section: Hsp60 Gw Shows An Increased Degree Of Surface Hydrophobicitysupporting
confidence: 89%
“…For instance, it has been demonstrated that a single mutation in HSP60 found in MitCHAP-60 destabilizes the chaperonin oligomers (Parnas et al, 2009 ). This is why in view of the potentially key roles of naïve HSP60 in cancer and other diseases, several studies have focused on its oligomeric organization and structure (Vilasi et al, 2014 ; Ricci et al, 2016 , 2017 ; Enriquez et al, 2017 ). A detailed study of the structure and self-organization of naïve cytosolic recombinant His-tag HSP60 in solution was performed, using biophysical methods such as Light and X-Ray Scattering, Single Molecule Spectroscopy, and hydrodynamics measurements (Vilasi et al, 2014 ).…”
Section: Hsp60 Outside Mitochondriamentioning
confidence: 99%
“…HSP60 at higher concentrations was analyzed by Small Angle X-Ray Scattering and, at lower concentrations was analyzed by Fluorescence Correlation Spectroscopy (Vilasi et al, 2014 ). In another laboratory, HSP60 was purified applying a protocol that yields HSP60 without the His6-tag (Enriquez et al, 2017 ). The results were similar to those described in the preceding lines, although a more marked difference between tetradecamer and heptamer concentrations was found.…”
Section: Hsp60 Outside Mitochondriamentioning
confidence: 99%
“…Group I chaperonins like the Escherichia coli chaperonin groEL and its co-chaperonin GroES (together denoted as groEL/ES), are typically found in eubacteria with the exception of the eukaryotic mitochondrial heat shock protein 60 (hsp60) and its co-chaperonin heat shock protein 10 (hsp60/10) (Fenton and Horwich, 1997 ). They are characterized as homo-tetradecamers composed of two stacked seven-membered rings (see Table 1 ) (Horwich et al, 2009 ; Enriquez et al, 2017 ). In addition, group I chaperonins possess a staggered (1:2) inter-ring subunit organization where one subunit in one ring directly contacts two subunits in the opposite ring (Braig et al, 1994 ; Ditzel et al, 1998 ; Hildenbrand and Bernal, 2012 ).…”
Section: Characteristics Of Group I and Ii Chaperoninsmentioning
confidence: 99%
“…Over the years, chaperonins with single-ring intermediates have been identified in eukaryotes and more recently in viruses (Horwich et al, 1993 ; Shaburova et al, 2006 ; Cornelissen et al, 2012 ; Hildenbrand and Bernal, 2012 ; Molugu et al, 2016 ; Semenyuk et al, 2016 ; An et al, 2017 ; Marine et al, 2017 ). Their protein-folding mechanisms, however, were poorly understood because they were largely based on knowledge obtained from studies of the bacterial groEL/ES chaperonin or its respective single-ring mutants (Sun et al, 2003 ; Liu et al, 2009 ; Kovács et al, 2010 ; Illingworth et al, 2011 , 2015 ; Enriquez et al, 2017 ). Recent cryo-EM structural analyses on the ϕ-EL phage-encoded chaperonin revealed that it undergoes ring dissociation to form single-ring intermediates upon ATP hydrolysis (Hertveldt et al, 2005 ; Kurochkina et al, 2012 ; Semenyuk et al, 2015 ; Molugu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%